Enhancing M currents: a way out for neuropathic pain? - Rivera-Arconada, Ivan; Roza, Carolina; Lopez-Garcia, Jose A. (Frontiers in Molecular Neuroscience, 2009)
Almost three decades ago, the M current was identified and characterized in frog sympathetic neurons (Brown and Adams, 1980). The years following this discovery have seen a huge progress in the understanding of the function and the pharmacology of this current as well as on the structure of the underlying ion channels. Therapies for a number of syndromes involving abnormal levels of excitability in neurons are benefiting from research on M currents. At present, the potential of M current openers as analgesics for neuropathic pain is under discussion. Here we offer a critical view of existing data on the involvement of M currents in pain processing. We believe that enhancement of M currents at the site of injury may become a powerful strategy to alleviate pain in some peripheral neuropathies.